EP 20. Contralesional Cathodal tDCS versus dual-tDCS for decreasing upper limb spasticity in chronic stroke individuals: A clinical and neurophysiological study. Issue 9 (September 2016) - Del Felice, A.; Daloli, V.; Masiero, S.; Manganotti, P.
Abstract : Background: Different transcranial direct current stimulation (tDCS) paradigms have been implemented to treat post-stroke spasticity, but discordant results have been reported. Objective: To determine the efficacy and persistence of dual-tDCS (anode over the affected motor cortex (M1) and cathode over the contralateral) compared to cathodal tDCS (cathode over contralateral M1) on upper limb (UL) functional, behavioral and neurophysiological measures in chronic post-stroke individuals. Methods: 10 subjects with UL spasticity (7 men; mean age 62 y; 8 ischaemic stroke; years from event: 2.3 y) were enrolled in a cross-over, double-blinded study. Cathodal tDCS and dual-tDCS, both preceded by one week of sham stimulation 1 month before real, were applied with a 3 months interval. Stimulating paradigm was 20 min for five consecutive days in each block. Evaluations were performed before treatment (T1), after real or sham treatment (T2), and after one (T3), four (T4) and eight weeks (T5). Functional, behavioral and neurophysiological tests were performed at each time. Results: Both tDCS paradigms decreased spasticity, increased strength and ameliorated behavioral scales. Cathodal tDCS was indeed superior to dual-tDCS in reducing UL distal spasticity immediately after treatment (T2: cathodal > dual: p  = 0.023), and providing a higher and longer lasting reduction at proximal districts (T3: cathodal > dual: 0.042; T4: cathodal > dual: 0.028; T5: cathodal > dual: 0.05). These findings are supported by a slight major effect of cathodal tDCS on H reflex modulation (overall time effect p  > 0.002). Conclusions: Cathodal tDCS is slightly more effective than dual-tDCS in reducing distal UL spasticity in chronic post-stroke subjects. A modulation of spinal inhibitory mechanisms, as demonstrated by H reflex modifications, supports this finding.